A case of extensive verrucosis in 45-year-old women and CD4 lymphopenia treated with electrodessication using general anesthesia and isoprinosine - Wahyu Lestari; Sri Lestari (Trends in Infection and Global Health, 2022)
The human papilloma virus (HPV) is a viral infection that has a broad variety of clinical manifestation. The clinical manifestation really depends on the type of HPV virus and the immunity status of the host, particularly the cell-mediated immunity. Extensive verrucosis is one of the significant clinical manifestation of a disseminated HPV infection that is related with a severe immunodeficiency status. Electrodessication or laser surgery is a method of treatment that could directly destroy the lesion in one time. We described a case of a 45 years-old woman with extensive verrucosis. The patient complained multiple warts lesion on the hands, face, neck, lower arms and lower extremities since eight years ago. Physical examination revealed on the dorsum and palmar hands, both of finger nails (I, II, III, and IV), face (forehead and cheeks), anterior of neck, lower arms and 2/3 distal of lower extremities part anterior, there were single and groups of flesh coloured papules and flesh coloured plaques, skin colour papules with flat topped, greyish papules and greyish plaques with verrucous surfaces and brownish crusts. The CD4 count of the patient was 91 cells/µL. Skin biopsy and histopathology examinations showed hyperkeratosis, papillomatosis, and acanthosis with vacuole cell (koilocytes). The patient was treated with electrodessication using general anaesthesia and isoprinosine 3x500 mg. The result after two weeks post-treatment showed that there were no new lesions appeared on post electro surgery site. This case highlights the importance of the treatment for the success of extensive verrucosis with CD4 lymphopenia.